Utilization of Livestock Manure for Fertilizer on Mustard Green and Lettuce as an Application of Cleaner Production - Nurmala Karima, Afifah; Oginawati, Katharina (Research of Environmental Science and Engineering, 2020)
Livestock waste is one of the sources of organic pollutants in surface and ground water. This entire time, the cattle owners in Dago Atas dispose the cattle manure directly into Cikapundung River without any treatment. Then it needs to be implementing a treatment technology to overcome the negative impact of the wastes disposal and to gain an added-value by recycling the livestock waste into organic fertilizer products. The solid fertilizers were made by mixing the manure with 5% Effective Microorganism 4 (EM4) of the total weight of the manure, while the liquid fertilizers weremade by adding 10% of EM4 into the cattle urine. To ensure that this technology appropriates to be applied, further research is needed in order to investigate the effect of the fertilizer utilization on the plant growth. The fertilizer in this research was implemented on the mustard greens and the lettuce crops. This research was arranged in a completely randomized factorial design with two factors: the first is a combination of the solid fertilizers dose and the second is a combination of the liquid fertilizer dose. The growth variables measured for each crop are the plant height per week, amount of leaves, total fresh weight, consume fresh weight, harvest index, and stem diameter. Based on the ANOVA test was concluded that the solid fertilizer effect on plant height, number of leaves, stem diameter, total weight and consume weight of mustard green. While on the lettuce, solid fertilizer effect on plant height, stem diameter, total weight, and consume weight. The use of liquid fertilizer had no effect on growth of mustard and lettuce. From the Duncan test, found that the best solid fertilizer dose in mustard green and lettuce is 4 kg/m2.